Recent developments, current challenges, and future directions in electrophysiological approaches to studying intelligence - Euler, Matthew J.; Schubert, Anna-Lena (Intelligence, 2021)
EEG studies represent an important sub-discipline in the field of intelligence research and have significant potential to advance the theoretical understanding and practical applications of the construct. This commentary reviews key themes and major developments in the field from the last several decades, and outlines open questions and future directions for the next phase of research. Two main areas of progress in recent years relate to (1) improvements in study design and psychometric approaches, and (2) increased integration with cognitive psychology and neuroscience. In turn, these advances have clarified several themes and pressing issues. These include: The need to establish the replicability and effect sizes of key effects, the need to explicitly attend to the distinction between trait- and task-related sources of variance in correlations between intelligence and EEG variables, the need to systematically identify and test moderators of those relationships, the need for greater use of formal modeling at the level of measurement and theory, and the need for continued integration of theoretical advances from related disciplines. We argue that an increased focus on these issues can yield rapid progress in this area over the coming years. The commentary concludes with suggestions for both immediate priorities and long-term directions in basic and applied EEG research on intelligence.
Gesehen am 17.11.2021